Performance of biodiesel blends on compression ignition engine - Rafidah, Rahim (2012)
The developments in alternative energy sources have become gradually more applicable with the increasing exploration for an adequate alternative to oil-based energy. The depletion of the amount of fossil fuels worldwide is steadily creating an incentive to replace them, either partially or completely, with bio-fuels. The purpose of this study is to define and provide a comparison for biofuels, mineral diesel (D2) and straight vegetable oil (SVO). The main properties of fuels have been investigated experimentally in the Chemical Laboratory of the University of Malaysia in Pahang. There are seven fuels, including 5% Biodiesel blended with 95% mineral diesel (B5), 15% Biodiesel blended with 85% mineral diesel (B15), 20% Biodiesel blended with 80% mineral diesel (B20), 50% Biodiesel blended with 50% mineral diesel (B50), 100% Biodiesel (B100), Straight Vegetable Oil (SVO), and Diesel fuel (D2). Tests were conducted to determine the effect of biodiesel blended with diesel fuel on the following properties: the energy content, density, cetane number, viscosity, cloud and pour point, flash point, acid value and moisture content. From the properties testing, the small proportions of biodiesel blended, which included B5, B15, B20 and D2, were analysed for their performance in GT-Power engine simulation. Subsequently, some of properties that have been determined earlier will be used as an input in a GT-Power simulation model. The GT-Power model was built for a single cylinder diesel engine. The input model’s engine specifications follow the diesel engine Yanmar TF-120M. Then the engine performance will be compared and discussed between the various blends of fuel. From the graph tendency, B5 is considerably pre-eminent for the good performance of the diesel engine. The higher energy content shows good agreement with the best performance of engine. This is because the lower energy content needs more BSFC to inject more fuel to gain equal brake torque and the same level of power. Nonetheless, the consequence of the lowest value of BSFC is obviously desirable. Attention was also alerted to the properties which influence the injection and engine characteristics extensively, thus affecting the quality of engine performance which also affects injector lubrication and fuel atomisation. Generally, biodiesel fuel blends can improve lubricant; nevertheless, the higher viscosity levels have a tendency to form larger droplets on injection that can cause exhaust smoke and poor combustion reactions.